Reptiles sold as traditional medicine in Xipamanine and Xiquelene Markets (Maputo, Mozambique). - Williams, V.L.; Moshoeu, T.J.; Alexander, G.J. (Academy of Science of South Africa (ASSAf), 2016)
Zootherapy plays a role in healing practices in Mozambican society. Although several studies have focused on ethnobotany and traditional medicine in the country, little research has been conducted on the use of reptiles in zootherapy. The aim of this study was therefore to fill this gap by assessing the reptile species traded for traditional medicine in the Xipamanine and Xiquelene Markets in Maputo, Mozambique. We found that few reptile species are traded domestically for traditional medicine and that their use appears to be in decline in Mozambique. Our findings also suggest that the domestic trade of reptiles for traditional medicines in Maputo markets is unlikely to have a significant impact on the conservation of reptiles in Mozambique. However, we suggest that international trade with South Africa is likely having a larger impact, given observations of Mozambican nationals selling a diverse range of fauna in urban traditional medicine markets in Johannesburg and Durban.
Keywords: Crocodylus; Ethnoherpetology; Python; Wildlife trade; Zootherapy